CHRONOS: A Schema-Based Event Understanding and Prediction System - Chang, Maria; Fokoue, Achille; Uceda-Sosa, Rosario; Awasthy, Parul; Barker, Ken; Kumaravel, Sadhana; Hassanzadeh, Oktie; Soares, Elton; Gao, Tian; Bhattacharjya, Debarun; Florian, Radu; Roukos, Salim (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Chronological and Hierarchical Reasoning Over Naturally Occurring Schemas (CHRONOS) is a system that combines language model-based natural language processing with symbolic knowledge representations to analyze and make predictions about newsworthy events. CHRONOS consists of an event-centric information extraction pipeline and a complex event schema instantiation and prediction system. Resulting predictions are detailed with arguments, event types from Wikidata, schema-based justifications, and source document provenance. We evaluate our system by its ability to capture the structure of unseen events described in news articles and make plausible predictions as judged by human annotators.